An in vitro system for human cytomegalovirus immediate early 2 protein (IE2)-mediated site-dependent repression of transcription and direct binding of IE2 to the major immediate early promoter. - Macias, M P (1993)
In vivo, negative autoregulation of the strong major immediate early promoter (MIEP) of human cytomegalovirus requires the viral immediate early 2 protein (IE2) and a cis element located from position -13 through position -1 relative to the transcription start site. We have established an in vitro transcription system that reproduces the specificity of IE2-mediated negative autoregulation. The carboxyl-terminal 290-amino acid fragment of IE2 was purified as a bacterial fusion protein. Addition of this chimeric protein to the cell-free system specifically repressed transcription from the MIEP containing the wild-type cis-acting repressor element but not from a mutated template in which the cis element had been replaced by heterologous DNA. Control protein and a mutant IE2 fusion protein containing two specific amino acid substitutions in a putative zinc finger motif did not repress the MIEP in vitro. Using conditions defined by this functional assay, we demonstrated by mobility-shift experiments that IE2 binds directly and specifically to DNA bearing the cis-acting repressor element. In addition, IE2 bound to the MIEP in the in vitro transcription reaction mixture.